Pulmonary high‐grade fetal adenocarcinoma associated with cystic airspace: A case report. Issue 6 (29th March 2020) - Ishida, Hironori; Yasuda, Masanori; Nitanda, Hiroyuki; Yanagihara, Akitoshi; Taguchi, Ryo; Yoshimura, Ryuichi; Umesaki, Tetsuya; Sakaguchi, Hirozo; Shimizu, Yoshihiko
Abstract: Lung cancers associated with cystic airspaces have a life‐threatening risk of a missed or delayed diagnosis. Here, we report a case of pulmonary high‐grade fetal adenocarcinoma, a rare lung carcinoma associated with cystic airspaces, as confirmed by computed tomography (CT) scan. A 73‐year‐old asymptomatic male with a 52‐pack a year smoking habit was referred to our hospital. Lung CT showed a thin‐walled cystic space with exophytic and endophytic solid nodules along the cyst wall. After surgery, histological analysis of a resected lung specimen revealed a pure high‐grade fetal adenocarcinoma probably associated with emphysematous bullae in pulmonary emphysema, suggesting smoking contributed to this pure form, as well as the emphysema. In conclusion, when treating elderly men with a smoking history, physicians need to carefully examine the walls of cystic airspaces on CT for fetal adenocarcinoma. Key points: Significant findings of the study Pulmonary high‐grade fetal adenocarcinoma may be associated with emphysematous bullae manifesting as cystic air spaces as shown by computed tomography. What this study adds When scanning by computed tomography, physicians should carefully examine the pulmonary cystic airspace walls in elderly men with a smoking history.